The Determinants of Consumer Attitude towards Mobile Payment Services - Hoang Thien Van, Huynh Cong Danh, Minh-Tung Nguyen, Hoang-Sy Nguyen (International Journal of Advanced Science and Technology, 2020)
Mobile Payment is a relatively new type of service, but it plays a vital role in the development of e-commerce in general. Therefore, evaluating the adoption level of mobile payment in the global economy as well as in Vietnam remains a meaningful topic. Based on the Theory of Planned Behavior (TPB), this paper provides a new explanation on the service-oriented attitude of the individual consumers for mobile payment based on the integration of three different angles: consumer innovativeness, perceived benefit and perceived risk. The SEM analysis of the sample of 250 individual consumers in Vietnam using Mobile Payment services indicated that five out of six hypotheses were to be supported. The result indicates that the proposed model can explain up to 49% the intention to reuse of mobile payment service. Moreover, as expected, consumer innovativeness and perceived benefit are positively correlated with the service-oriented attitude in mobile payment, while the perceived risk is negatively correlated.